Diffusion tensor imaging findings suggestive of white matter alterations in a canine model of mucopolysaccharidosis type I. Issue 1 (February 2018) - Middleton, Dana M; Li, Jonathan Y; Chen, Steven D; White, Leonard E; Dickson, Patricia; Ellinwood, N Matthew; Provenzale, James M
Purpose: We investigated fractional anisotropy (FA) and radial diffusivity (RD) in a canine model of mucopolysaccharidosis (MPS). We hypothesized that canines affected with MPS would exhibit decreased FA and increased RD values when compared to unaffected canines, a trend that has been previously described in humans with white matter diseases. Methods: Four unaffected canines and two canines with MPS were euthanized at 18 weeks of age. Their brains were imaged using high-resolution diffusion tensor imaging (DTI) on a 7T small-animal magnetic resonance imaging system. One hundred regions of interest (ROIs) were placed in each of four white matter regions: anterior and posterior regions of the internal capsule (AIC and PIC, respectively) and anterior and posterior regions of the centrum semiovale (ACS and PCS, respectively). For each specimen, average FA and RD values and associated 95% confidence intervals were calculated from 100 ROIs for each brain region. Results: For each brain region, the FA values in MPS brains were consistently lower than in unaffected dogs, and the RD values in MPS dogs were consistently higher, supporting our hypothesis. The confidence intervals for affected and unaffected canines did not overlap in any brain region. Conclusion: FA and RD values followed the predicted trend in canines affected with MPS, a trend that has been described in humans with lysosomal storage and dysmyelinating diseases. These findings suggest that the canine model parallels MPS in humans, and further indicates that quantitative DTI analysis of such animals may be suitable for future study of disease progression and therapeutic response in MPS.